Relatório de Estágio Profissional "Ser Professor: a Longa-Metragem entre o sonhar e o concretizar de um sonho ..." - Rui Celso da Costa Rodrigues (2019)
The professional internship is the space where new experiences with to unknown are provided and knowledge that will serve as a fundamental instrument in the future. Here begins a new path for the student intern involving the implementation of the theory in real context. All this phase that accompanies the life of each teacher does not end with the end of classes, but after the completion of the Internship Report, which describes all experiences, acquired knowledge and reflections. Therefore, this document, under the guidance of the Advisor and Cooperating Professor, is based on the existing literature on the internship, pedagogy and didactics, critically reflecting all the experience acquired in this process. In this sense, the report was subdivided into five chapters and described below. The first chapter, "Introduction", sets out the purpose of this document. The second, "Personal Dimension", refers to aspects such as my lifelong journey, as well as some sporting experiences in which I participated, the experiences that led to my professional choice, the expectations for this new experience and the role of the internship itself. "Institutional Dimension" is part of the third chapter that addresses the role of the professional internship in the aspects: institutional, legal, and some information about the Internship Center. The fourth chapter, the "Operational Dimension" encompasses three areas, 1, 2 and 3, containing information on the preparation, implementation and evaluation of teaching, as well as a description of the various school activities developed in the school context. The third area includes an action research study where, through the implementation of different teaching approaches based on the teacher and the student, it was intended to perceive the students' motivation levels, according to the method used. In the fifth and final chapter, "Conclusions and Prospects for the Future", an assessment is made of the end of the probationary year, including a balance of goal setting, insights into my personal evolution and aspirations for the future.